Does approach bias modification really work in the eating domain? A commentary on Kakoschke et al. (2017). (February 2018) - Becker, Daniela; Jostmann, Nils B.; Holland, Rob W.
Highlights: The review prematurely concludes that the training works in the eating domain. No (eating domain) study with a 'sham training' control group found effects. All (eating domain) studies with no or a suboptimal control group found effects. More well-designed research necessary to judge effectiveness in eating domain